Practical Asymmetric Fluorination Approach to the Scalable Synthesis of New Fluoroaminothiazine BACE Inhibitors - Garcia-Losada, Pablo; Barberis, Mario; Shi, Yuan; Hembre, Erik; Alhambra Jimenez, Carolina; Winneroski, Leonard L; Watson, Brian M; Jones, Chauncey; DeBaillie, Amy C; Martínez-Olid, Francisco; Mergott, Dustin J (Organic process research & development, 2018)
Here we report an optimized protocol for the asymmetric introduction of a fluorine atom into a quaternary center facilitated by d-proline, Selectfluor®, and trifluoroethanol. The synthesis proceeds over four steps starting from a chiral amino alcohol precursor and provides the desired enantiomer with no erosion of chiral purity and good diastereoselectivity. The process optimization allowed diastereoselective preparation of the key intermediate on a multigram scale.